RANCANG BANGUN MINI TRAINER PRESSURE SENSOR SEBAGAI MEDIA PEMBELAJARAN - Ronald Lorenzo; Irma Yulia Basri; Dony Novaliendry; Dedy Irfan (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Learning Media is a very important thing in the teaching and learning process, with the learning media students can understand learning better. The types of Pressure Sensors in the Department of Automotive Engineering, Padang State University have not been there, so students are not able to understand the concept of the characteristics still constrained. This study uses research and development methods (Research and Development) which aims to determine the performance, feasibility level of Basic Concept Trainer. Data retrieval is done 4 times in each test, raw data obtained during testing are processed with several stages of testing: Accuracy Test, Repeability Test, Linearity Test, Test the level of eligibility based on the opinion of experts and users. The results of the trainer performance of the basic concept of the pressure sensor, it is known that the accuracy test shows the average percentage accuracy is 99.45%, the linearity test data is linear, the repeatability test is obtained by 0.009, the feasibility level of the Trainer Basic Concepts of Pressure Sensors from 4 media experts in the category Very Eligible (91.81%), the feasibility level of the Basic Pressure Sensor Trainer concept from users in the Very Eligible category (92.93%).